Serological evidence of exposition to Toxoplasma gondii in Saimiri spp. kept in a research institution as biomodels in Rio de Janeiro - de Oliveira, Carolina Andrade; Arruda, Igor Falco; da Silva Barbosa, Alynne; de Abreu Pissinatti, Thalita; Langoni, Helio [UNESP]; Amendoeira, Maria Regina Reis (Wiley, 2024)
Anti-Toxoplasma gondii antibodies were investigated in 125 Saimiri spp. kept at a research institute. A total of 12% of primates tested positive, all of which were Saimiri sciureus. These results highlight the need to minimize the possibility of this protozoan's circulation, which can lead to fulminant infection in these animals.
Keywords: serology; squirrel monkeys; toxoplasmosis